MANAGING COHERENCE AND FLUENCY THROUGH DISCOURSE MARKERS IN UNIVERSITY EFL STUDENTS’ ACADEMIC ORAL PRESENTATIONS: A PRAGMATIC DISCOURSE ANALYSIS - Arni Alfina Damayanti; Khoirul Huda; Buyun Khulel (Universitas Muhammadiyah Metro, 2026)
EFL university students frequently struggle to maintain coherence and fluency simultaneously during academic oral presentations, yet the pragmatic role of discourse markers in addressing this challenge remains underexplored in the Indonesian EFL context. This study investigated the types of discourse markers employed by EFL students, their pragmatic functions in supporting discourse coherence, and their contribution to fluency maintenance during academic oral presentations. A qualitative descriptive design was employed, applying Pragmatic Discourse Analysis as the analytical framework, drawing on the theoretical foundations of (Fraser, 1990) and (Schiffrin, 1987). The participants were 14 fifth-semester undergraduate students of the English Language Education Program at Universitas Islam Darul Ulum (UNISDA), Lamongan, Indonesia, at an intermediate level of English proficiency. Data were collected through audio recording and verbatim transcription of classroom presentations, using a researcher-developed Discourse Marker Identification Checklist and Coding Scheme. Data were analyzed through systematic identification, classification, and pragmatic interpretation across all transcripts. The findings revealed five functional categories: additive (31.19%), causal (21.56%), sequential (17.43%), elaborative (16.51%), and contrastive (13.30%), across 218 total instances. These markers functioned to organize discourse structure, signal logical relationships, and sustain speech fluency simultaneously. A key limitation is the small, institution-specific sample. The study concludes that discourse markers serve as integrative pragmatic devices managing coherence and fluency concurrently. EFL educators should integrate explicit instruction on all five discourse marker categories into academic speaking curricula. While future research should expand to larger, multi-institutional samples using mixed-method designs.